Sexual Orientation Discrimination and Autonomy of Religious Groups in the Inter-American Case Law - Arlettaz, Fernando (The Age of Human Rights Journal, 2023)
Religious freedom encompasses the right of religious groups to define the tenets of their faith andto organise themselves according to these tenets, without arbitrary State interference. However, the limitsof religious groups’ autonomy are controversial, especially in those cases where the exercise of religiousautonomy seems to be at odds with non-discrimination standards. The Inter-American Court of HumanRights has adopted many decisions on sexual orientation discrimination, but its case law on religiousfreedom is much scarcer. The two issues converged in the recent decision Pavez Pavez v Chile, in which theCourt set the limits of the autonomy of religious groups when confronted with non-discrimination standards.